ANALYSIS OF SOLAR REFRIGERATION SYSTEM USING THERMO ELECTRIC COOLING (TEC) MODULE - Sutar Rajshekhar Manohar; Rajamane Nitish Mallikarjun; Gobbur Akshay Sidharam; Gadkar Pradip Vyankatesh (International Journal of Innovations in Engineering Research and Technology, 2021)
A refrigerator is a common house hold appliance that consists of a thermally insulated compartment and a heat pump that transfer heat from the inside of the refrigerator to its surrounding so that the inside of the refrigerator is cooled to a temperature below the ambient temperature of the room. Thermoelectric Cooling (TEC) solar refrigerator runs on energy provided by sun, which includes photovoltaic or solar thermal energy. Peltier Jean (1834) discovered the Thermoelectric (TE) property about two centuries ago;thermoelectric device havecommercialized during recent years. The applications of TE vary from small to large refrigerators. The Thermoelectric module refrigerator work on the principle of Peltier effect. Recently, the application of TEC modules in an industry is dramatically increased. Theyhave been adopting the solar refrigeration, widely recognized as alternative to the conventional vapourcompression system for their merits of energy saving and being eco-friendly. The paper presents a design of TEC solar refrigeration using thermoelectric cooling. The objective of this paper is to establish an alternative eco-friendly refrigeration cycle for producing a temperature usually encountered in a conventional refrigerator. By designing and manufacturing such type of refrigerator adds new dimension to the world of refrigeration. The proposed solar refrigeration system using TEC module is a feasible alternative for local refrigeration system. Briefly,the paper presents an economical and feasible model of solar refrigeration system.